Increasing Farmers' Knowledge in Making Super Local Chicken Feed in Watubangga Village, Baruga District, Kendari City - Pagala, Muhammad Amrullah; Saili, Takdir; Asminaya, Nur Santy; Badaruddin, Rusli; Syamsuddin; Muh. Munadi, La Ode (PT FORMOSA CENDEKIA GLOBAL, 2024)
This service was carried out in Watubangga Village, Baruga District, Southeast Sulawesi Province. This Community Service (PKM-MD) program applies group counseling methods with non-physical and physical activities to increase farmers' understanding of feed quality and the potential of local resources as raw materials. The outreach is designed to increase farmers' awareness of the importance of understanding animal feed. In addition, this program provides knowledge about local resources that can be used as alternative feed, which are rich in nutrients and can be processed into quality feed. It is hoped that through this activity, farmers can improve the quality of their animal feed, reduce the risk of disease, and increase the productivity of livestock businesses in a sustainable manner.